APLIKASI E-COMMERCE BERBASIS WEBSITE DI AEERASKINCARE MALANG - Eka Yulia Orbaningtyas; Jauharul Maknunah; Nasrul Firdaus (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2025)
It has been almost 3 years since Aeeraskincare has been selling its skin care products in the market. Even though Aeeraskincare has been selling its products for a long time, there are still some obstacles in selling its products. One of the problems comes from the marketplace, which often deletes some of the products it sells without explaining the reason for the deletion of the product. The removal of some products caused sales to decline. In addition, there is still a lack of promotion and Aeeraskincare does not yet have its own website, so there are still many people who do not know Aeeraskincare. In the delivery of product information is still lacking in detail about the benefits contained in the product. In recording sales data, Aeeraskincare still uses the manual method so that errors often occur in recording. With the creation of this e-commerce application, it can be used as a solution to assist in the promotion and also the sales system at Aeeraskincare. In testing the e-commerce application at Aeeraskincare Malang, 50% of the results stated that it was very helpful. So it can be concluded that the e-commerce application in Aeeraskincare Malang is very helpful for consumers.